The History of Behavioral Treatments in Autism: From the Punitive to the Positive - Suppo, Jennifer L. (Journal of the American Academy of Special Education Professionals, 2017)
The behavioral treatments for persons diagnosed with autism have evolved from those that included punitive components to those that are now based upon principles of positive behavior supports. The proceeding document provides an historical overview of relevant behavioral approaches, including the type of approach and the quality of involvement and roles of the family, the professional, and of the individual with autism. In order for practitioners to make informed decisions in deciding the individualized course of treatment for a person with autism, they need to ascertain a good working knowledge of available methods of treatment.